SPE Annual Technical Conference and Exhibition 2002
DOI: 10.2118/77440-ms
|View full text |Cite
|
Sign up to set email alerts
|

Microseismic Imaging of Hydraulic Fracture Complexity in the Barnett Shale

Abstract: Microseismic monitoring has been used to image hydraulic fracture growth in the Barnett Shale. The Barnett is a naturally fractured shale reservoir, which causes significant complexity in fracture growth during well stimulation operations. Several Barnett treatments have been successfully imaged between March 2000 and December 2001. In this paper, examples will be given to illustrate the complexity and variability which is developed during the treatment as the slurry interacts with the pre-existing fracture se… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
81
0

Year Published

2007
2007
2023
2023

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 273 publications
(82 citation statements)
references
References 3 publications
1
81
0
Order By: Relevance
“…These include: (i) how best to address, in a numerically efficient and physically realistic manner, the handling of layer debonding and fluid invasion along layer interfaces with associated stunting of fracture height growth in shallower wells-relatively limited progress has been made in this area [94][95][96]; (ii) how to appropriately adjust current (linear elastic) simulators to enable modeling of the propagation of hydraulic fractures in highly cleated coal bed seams (for the extraction of methane) [97]; (iii) how to appropriately adjust current (linear elastic) simulators to enable modeling of the propagation of hydraulic fractures in weakly consolidated and unconsolidated ''soft'' sandstones, such as are found in the Gulf of Mexico-limited progress has been made in this area [98,99]; (iv) laboratory and field observations demonstrate that mode III fracture growth does occur [100], and this needs to be further researched; (v) related to (iii), the effect of the invaded zone ahead of the fracture tip needs to be further researched-a criterion to switch from a fluid lag based approach to an invaded zone based approach in a numerical model is required; (vi) suitable models for the propagation of hydraulic fractures in naturally fractured reservoirs that result in complex (non-planar) geometric configurations requires development [101]; and (vii) how to efficiently model 3D or ''out of plane'' effects, such as fracture re-alignment (when the fracture initiates following an orientation that is not perpendicular to the minimum in situ stress and then tries to re-align itself), which could be a cause of near-wellbore tortuosity or even ''pinching,'' a factor that usually determines the success or failure of hydraulic fracturing treatments [102].…”
Section: Discussionmentioning
confidence: 99%
“…These include: (i) how best to address, in a numerically efficient and physically realistic manner, the handling of layer debonding and fluid invasion along layer interfaces with associated stunting of fracture height growth in shallower wells-relatively limited progress has been made in this area [94][95][96]; (ii) how to appropriately adjust current (linear elastic) simulators to enable modeling of the propagation of hydraulic fractures in highly cleated coal bed seams (for the extraction of methane) [97]; (iii) how to appropriately adjust current (linear elastic) simulators to enable modeling of the propagation of hydraulic fractures in weakly consolidated and unconsolidated ''soft'' sandstones, such as are found in the Gulf of Mexico-limited progress has been made in this area [98,99]; (iv) laboratory and field observations demonstrate that mode III fracture growth does occur [100], and this needs to be further researched; (v) related to (iii), the effect of the invaded zone ahead of the fracture tip needs to be further researched-a criterion to switch from a fluid lag based approach to an invaded zone based approach in a numerical model is required; (vi) suitable models for the propagation of hydraulic fractures in naturally fractured reservoirs that result in complex (non-planar) geometric configurations requires development [101]; and (vii) how to efficiently model 3D or ''out of plane'' effects, such as fracture re-alignment (when the fracture initiates following an orientation that is not perpendicular to the minimum in situ stress and then tries to re-align itself), which could be a cause of near-wellbore tortuosity or even ''pinching,'' a factor that usually determines the success or failure of hydraulic fracturing treatments [102].…”
Section: Discussionmentioning
confidence: 99%
“…Microseismic measurements and other evidences [1,2] have confirmed that the creation of a complex fracture network during fracture treatment is a common occurrence in unconventional ultra-low permeability shale reservoirs. It has long been observed in mine-back and fracture core-through experiments [3][4][5][6] that the interaction between hydraulic fracture (HF) and the pre-existing natural fracture (NF) in the shale are the likely reason of forming this complex fracture network.…”
Section: Introductionmentioning
confidence: 78%
“…Besides direct observations in neighboring wells [7], microseismicity [8][9][10][11], tilt mapping [7], treatment pressure analysis [7], production data [7], and reservoir modeling [13] from hydraulic fracturing treatments in many geological environments also support the observation of complex fracture network development at macro scale. The most important natural factors triggering hydraulic fracture complexity were found to be discontinuities (joints, faults, bedding planes) and heterogeneities within the rock mass [3] in conjunction with the in-situ stress field (e.g.…”
Section: Introductionmentioning
confidence: 99%
“…Chen et al [14]). Environments where complex fracture networks may be formed include shale formations such as the Barnett shale [11,7] and granitic basement rock [13].…”
Section: Introductionmentioning
confidence: 99%